Netralitas Aparatur Sipil Negara Kantor Sekretariat Daerah Kabupaten Minahasa Tenggara Pada Pemilihan Gubernur Dan Wakil Gubernur Provinsi Sulawesi Utara Tahun 2015 - Gosal, Fidel; Lengkong, Florence Daicy; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: December 9, 2016 is the day of the General Election of Regional Head simultaneouslythroughout Indonesia. One of the areas that implement Regional Head Election is the province ofNorth Sulawesi. Based on the results study Bawaslu North Sulawesi there are many districts /municipalities in North Sulawesi were prone to problems in the Regional Head General Election.From the results of this study Southeast Minahasa is a region prone to 4th highest problems in theprocess of Regional Head General Election. In addition to money politics, the neutrality of the StateCivil Apparatus is one of the most common problems occur in the Regional Head General Electionin Southeast Minahasa Regency. Recognized by one of the State Civil Apparatus that violations do isfollow the campaign with the party attributes and participate in supervising the voting results onElection Day took place. This happens because there is intervention from the employer to the chiefof the District is forwarded to the State Civil Apparatus in each office. As for the purpose of thisresearch was to determine how the neutrality of the State Office of Administrative Civil SecretariatSoutheast Minahasa regency in the election of Governor and Vice Governor of North Sulawesiprovince in 2015 The research method in this study is qualitative research methods and datacollection techniques in this study is the observation / direct observation of localized research,conduct interviews, and documentation. The results showed there were several State Civil Apparatus2015 that violated the rules on the election in the area. The factors that influence that the Stateviolated the Civil Aparatur Regional Head Election process takes place is a rule which does notprovide clear boundaries between political and administrative domain, the intervention of politicalparties, and individual interests.Keywords: Neutrality Civil State Apparatus, the election of Governor and Vice Governor